Planning for Degrowth in Big Chinese Cities - Xue, Jin (AESOP, 2012)
Discourses on sustainability have led to the development of two distinct ideal societal paradigms: ecological modernization and ecosocialism. Urban planning is on one hand defined by the features of a certain paradigm and on the other hand a vehicle inspiring changes towards that paradigm. China’s recent shift in development path as a response to social and environmental issues has a strong salience of ecological modernization, evident in the newly enacted national territory development plan. However, the emphasis on promoting competitiveness in wealthy coastal cities and extending economic growth to inland China is argued to be environmentally and socially unsustainable in the long run. For long-term sustainability, economic non-growth/degrowth is necessary in affluent cities, while growth opportunities should be directed to poorer regions. This requires a degrowth planning agenda in China and changes in planning rationality and spatial logics nationwide. Such an alternative path aligns with the ecosocialism paradigm, and China’s economic-political conditions and traditional philosophies offer potential for this transition.
Book of proceedings : AESOP 26th Annual Congress 11-15 July 2012 METU, Ankara
Keywords: China; ecological modernization; ecosocialism; urban planning; degrowth